Menjembatani Kesenjangan : Kerangka Kerja SDG-Wakaf-FinTech Terpadu untuk Transformasi Keuangan Pendidikan di Indonesia - Rifaldi Nurul Akbar; Muhammad Iman Kurniawan; Miftah Hur Rahman Zh; Athia Nur Kamilah (UIN AM. Sangadji Ambon, 2025)
This study investigates the convergence of Islamic social finance, educational waqf, and FinTech to finance Sustainable Development Goal (SDG) 4 in Indonesia. It aims to map the potential and challenges of this integration and propose a synergistic conceptual model. Employing a qualitative approach, we collected primary data through in-depth interviews with 25 key stakeholders, Focus Group Discussions (FGDs), and analysis of policy documents. Thematic analysis reveals that the potential of educational waqf is hampered by regulatory asymmetry and governance deficits within the nadzir institution, leading to a strategic misalignment with specific SDG 4 targets. Our findings identify the dual role of FinTech as a capital mobilizer via micro-waqf platforms and as a blockchain-based monitor that builds transparency. The study concludes that realizing an effective waqf ecosystem requires an integrated approach: strengthening regulatory foundations and nadzir capacity, leveraging FinTech as a catalyst, and adopting an SDG-aligned impact measurement framework. Future research should prioritize developing and testing such a measurement framework and exploring regulatory sandbox models for Shari'ah-compliant waqf FinTech innovation. Keywords: Educational Waqf, FinTech, SDG 4, Governance, Blockchain, Impact Measurement, Islamic Social Finance